Pengaruh Pemberian Kompensasi dan Motivasi Kerja terhadap Kepuasan Kerja pada PT. Kirana Swasti Parama - Indra Mulyawan; Nurvi Oktiani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to find out whether there is an effect of compensation and work motivation on job satisfaction at PT. Kirana Swasti Parama. The research method used is a quantitative method with a data collection method through questionnaires. The data analysis technique used is the likert scale. The data source used is primary data with the help of statistical data analysis tools of the SPSS Version 26 program and the sample used in this study consists of 30 respondents. The variables used were independent, namely compensation (X1) and work motivation (X2), and the dependent variable was job satisfaction (Y). The results of the study on multiple linear regression analysis show the regression equation Y = 1.450 + 0.413 X1 + 0.539 X2. The results of the t-test result showed that tobtained > ttable (3.132 > 2.04523) for compensation for job satisfaction and the tobtained > ttable (4.617 > 2.04523) for motivation for job satisfaction, which means that there was an effect of compensation and work motivation on job satisfaction. The results of the F test showed a value of fobtained > ftable (104,747 > 3,354), meaning that the provision of compensation and work motivation had a great influence on the job satisfaction of employees of PT. Kirana Swasti Parama.